Stages of endometriosis: Does it affect in vitro fertilization outcome - Sonja Pop-Trajkovic; Jasmina Popović; Vladimir Antić; Dragana Radović; Milan Stavanovic; Predrag Vukomanović (Elsevier, 2014)
Objective: Women with endometriosis often need in vitro fertilization (IVF) to conceive. There are conflicting data on the results of IVF in patients with endometriosis. The present study was undertaken to investigate whether or not the stage of endometriosis affects the IVF outcome in order to give the best patient counseling Materials and methods: We compared IVF outcome measures between 40 patients with surgically confirmed minimal and mild endometriosis (American Society for Reproductive Medicine Stage I/II) and 38 patients with moderate and severe endometriosis (Stage III/IV). Each group was also compared with a control group of 157 patients with tubal factor infertility. Outcome measures included number of follicles, number of oocytes, mean number of ampoules of gonadotropins, cumulative pregnancy, and live birth rates Results: Higher cancelation rates, higher total gonadotropin requirements, and lower oocyte yield were found in women with endometriosis Stage III and IV compared with both the Stage I/II and control groups. The fertilization rate was higher in Stage III/IV endometriosis compared to Stage I/II. Clinical pregnancy and live birth rates were comparable between patients with endometriosis Stage I/II and control group, whereas they were significantly lower in patients with endometriosis Stage III/IV compared to other two groups. Conclusion: The American Society for Reproductive Medicine classification of endometriosis is useful in predicting IVF outcome. Advanced endometriosis means a worse prognosis for IVF treatment compared to milder stages or tubal factor infertility. The decreased fertilization rate in Stage I/II endometriosis might be a cause of subfertility in these women, as a result of a hostile environment caused by the disease.